Political Orientation of Government and Stock Market Returns - Jedrzej Bialkowski; Katrin Gottschalk; Tomasz Piotr Wisniewski (European University Viadrina, The Postgraduate Research Programme: Capital Markets and Finance in the Enlarged Europe, 2006)
Prior research documented that U.S. stock prices tend to grow faster during Democratic administrations than during Republican administrations. This letter examines whether stock returns in other countries also depend on the political orientation of the incumbents. An analysis of 24 stock markets and 173 different governments reveals that there are no statistically significant differences in returns between left-wing and right-wing executives. Consequently, international investment strategies based on the political orientation of countries' leadership are likely to be futile.
Keywords: G14; G11; G15; 330; Stock market returns; Politics; Presidential puzzle